2008
DOI: 10.1080/00365590801943274
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral estrogen versus combined androgen deprivation in the treatment of metastatic prostatic cancer: Part 2. Final evaluation of the Scandinavian Prostatic Cancer Group (SPCG) Study No. 5

Abstract: PEP has an anticancer efficacy equal to CAD and does not increase cardiovascular mortality in metastasized patients, but carries a significant risk of non-fatal cardiovascular events, which should be balanced against the skeletal complications in the CAD group. It is feasible to use Estradurin in the primary or secondary endocrine treatment of metastasized patients without prominent cardiac risk factors and especially those with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 25 publications
0
38
0
4
Order By: Relevance
“…Clinical studies comparing estrogen to other forms of ADT have shown that men treated with estrogen are less troubled by hot flashes (Spetz et al 2001, Hedlund et al 2008, Langley et al 2013. In SPCG-5, 70% of men receiving PEP were free of hot flashes compared to 26% of men receiving CAB.…”
Section: :8mentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical studies comparing estrogen to other forms of ADT have shown that men treated with estrogen are less troubled by hot flashes (Spetz et al 2001, Hedlund et al 2008, Langley et al 2013. In SPCG-5, 70% of men receiving PEP were free of hot flashes compared to 26% of men receiving CAB.…”
Section: :8mentioning
confidence: 99%
“…In comparison to high-dose synthetic oral estrogens, LHRHa had the advantage of relative cardiovascular safety and less gynaecomastia, at the significant cost of more VMS and osteoporosis (Leuprolide Study Group 1984, Ockrim et al 2006, Hedlund et al 2008. These side effects ensured that interest in estrogen as an alternative continued.…”
Section: Past and Present Endocrine Treatments For Prostate Cancermentioning
confidence: 99%
See 3 more Smart Citations